Active packaging based on cellulose trays coated with layered double hydroxide as nano‐carrier of parahydroxybenzoate: Application to fresh‐cut iceberg lettuce. Issue 6 (2nd March 2021) - Viscusi, Gianluca; Bugatti, Valeria; Gorrasi, Giuliana
Abstract : Layered double hydroxide (LDH) as nano‐carrier of parahydroxybenzoate (listed in EC Directive 10/2011) was coated on a biodegradable film of cellulose acetate, coupled with compostable cellulose cardboard and trays realized. The sustained release of parahydroxybenzoate ionically intercalated into the LDH resulted significantly slower than the parahydroxybenzoate free dispersed into the coating medium. Such active packaging showed significant antimicrobial activity against Salmonella enterica Typhimurium, Escherichia coli, Listeria monocytogenes and Lactobacillus sakei . It was more than one in all cases, ranging from 1.1 for E. coli to 2.6 for S. enterica Typhimurium. Overall migration tests in ethanol at 50% (v/v), as food simulant, showed that the prepared packaging is suitable for food contact, being the migrated amount below the limits imposed by the EU regulation. Fresh‐cut iceberg lettuce was packed into the prepared active packaging and in a control packaging with no active coating and stored in condition of thermal stress (i.e. 10°C). Organoleptic characteristics and the evolution up to 14 days of mesophilic lactic bacteria, total bacteria count, yeasts and moulds showed a significant inhibition of such strains from the active filler. Comparing the lettuce packed in control and active packaging, for mesophilic lactic bacteria, it was found a delta log of 0.24 (CFU), and for the total bacteria count, a delta log of 1.63 (CFU). The most significant effects were observed respect to yeasts and moulds and yeasts counts. For yeasts, it was observed a delta log of 2.32 (CFU), and for yeasts and moulds, a delta log of 2.5 (CFU). The prediction of the shelf life of the lettuce was done following the growth of E. coli up to 30 days through the Gompertz equation. It was found a prolongation of the shelf life from 11 to 16 days Abstract : Cellulose acetate coated with LDH‐parahydroxybenzoate was prepared. Iceberg lettuce (Il) was coupled with trays of compostable cellulose cardboard. Il was packaged in thermal stress conditions (i.e. 10°C). The shelf life, evaluated considering coliforms, was extended up to 16 days.